ANALISIS PROSES BERPIKIR SISWA DALAM PEMECAHAN MASALAH TERBUKA BERBASIS POLYA SUB POKOK BAHASAN TABUNG KELAS IX SMP NEGERI 7 JEMBER - Safrida, Lela Nur; Susanto, S; Kurniati, Dian (Kadikma, 2015)
Abstract. The research aims to describe the students’ thinking process of 9th grade of Junior High School in solving the open problem according to their capability in solving problem based on Polya’s solution step. Data analysis is done based on written test and interview techniques. The subject of research is students of IXA class at SMPN 7 Jember in odd semester academic year 2013-2014. The data of research are obtained by validation sheet, written test, and interview techniques. Students experience disequilibrium when they don’t understand about the qestion’s sentence and when she can’t determine the ways to solve the problem, also when she can’t determine the ways to check the result that has already gotten when she does the plans. Students experience assimilation when they can mention what is known and what is asked  from the problems immediately without reck of true or false, also when  they can determine the ways to solve the problems and when they are doing the computations. Students experience accomodation when they are quiet and confuse before they can determine the problem’s condition, also when she is doing the computation and when she is quite before she can determine the ways to solve the problem. Students experience assimilation and accomodation to reach the equilibrium phase. Key Words: thinking process, open problem, and Polya’s solution step.